1996
DOI: 10.1021/cm9501731
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering of Noncentrosymmetric Structures Based on 2-Amino-5-nitropyridine and n-Chloroacetic Acid Assemblies

Abstract: New noncentrosymmetric crystals including the 2-amino-5-nitropyridinium and 2-amino-5-nitropyridine chromophores have been designed following a strategy first applied to the 2-amino-5-nitropyridinium dihydrogen phosphate. If a counteranion able to self-aggregate in chains or layers as (H 2 PO 4 -) n is associated to the 2-amino-5-nitropyridinium cation, a noncentrosymmetric structure based on herringbone motifs is systematically formed. In the same way it has been observed that a bulky group grafted on the ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Because BO 4 tetrahedra are considered weak SHG originators, the NLO effect in SCB likely originates from tartrate groups. Furthermore, Nicoud et al have suggested that organic groups grafted on an inorganic framework are always associated with a NCS crystal structure. Additionally, the presence of delocalized π-electron systems, which enhance asymmetric polarizability, is the primary reason for the nonlinearity in organic materials, and such measurements also help to confirm the assignment of this structure in a NCS setting.…”
Section: Resultsmentioning
confidence: 99%
“…Because BO 4 tetrahedra are considered weak SHG originators, the NLO effect in SCB likely originates from tartrate groups. Furthermore, Nicoud et al have suggested that organic groups grafted on an inorganic framework are always associated with a NCS crystal structure. Additionally, the presence of delocalized π-electron systems, which enhance asymmetric polarizability, is the primary reason for the nonlinearity in organic materials, and such measurements also help to confirm the assignment of this structure in a NCS setting.…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that 2-aminopyrimidine and, often, carboxylic acids exist as hydrogen-bonded dimers in their homomeric crystal structures, she reasoned that they might form heteromeric dimers which would be supramolecular heterosynthons for new structures (Figure ). That proved to be the case, leading to the discovery of new, 2-aminopyrimidine-containing cocrystals in her laboratories as well as by other research groups (Table ). Similarly, carboxylic acids were found to form supramolecular heterosynthons with other functionalized heterocyclic bases such as 2-amino-5-nitropyridine and 2-pyridone . Cocrystals containing other hydrogen bonding patterns were constructed by similar analyses of homomeric structures, examples being the cocrystals containing 2-aminopyrimidones and dicarboxylic acids …”
Section: Cocrystals Containing All Organic Componentsmentioning
confidence: 94%
“…The use of similar building blocks in crystal engineering (notably in the design of non-linear optical materials) has received widespread attention and many groups are making important contributions to our understanding of exercising precise control over interplanar distances, layer topology and other structural features that eventually determine the physical properties of these materials (Zyss, Pecaut, Levy & Masse, 1993;Watanabe, Noritake, Hirose, Okada & Kurauchi, 1993;Kadirvelraj, Umarji, Robinson, Bhattacharaya & Guru Row, 1996;Bhattacharaya, Dastidar & Guru Row, 1994;Lefur, Bagieu-Beucher, Masse, Nicoud & Levy, 1996). Although these structures contain several predictable structural features, they do not represent materials over which we can claim complete control.…”
Section: Ionic Organic Compoundsmentioning
confidence: 99%